# Solve the Following Equation and Verify Your Answer: ( 2 X + 3 ) − ( 5 X − 7 ) 6 X + 11 = − 8 3 - Mathematics

Sum

$\frac{(2x + 3) - (5x - 7)}{6x + 11} = - \frac{8}{3}$

#### Solution

$\frac{(2x + 3) - (5x - 7)}{6x + 11} = \frac{- 8}{3}$

$\text{ or }\frac{- 3x + 10}{6x + 11} = \frac{- 8}{3}$

$\text{ or }- 9x + 30 = - 48x - 88 [\text{ After cross multiplication }]$

$\text{ or }- 9x + 48x = - 88 - 30$

$\text{ or }39x=-118\text{ or }x=\frac{- 118}{39}$

$\text{ Thus, }x = \frac{- 118}{39}\text{ is the solution of the given equation .}$

$\text{ Check: }$

$\text{ Substituting }x = \frac{- 118}{39}\text{ in the given equation, we get: }$

$\text{ L . H . S . }= \frac{- 3(\frac{- 118}{39}) + 10}{6(\frac{- 118}{39}) + 11} = \frac{354 + 390}{- 708 + 429} = \frac{744}{- 279} = \frac{- 8}{- 3}$

$\text{ R . H . S .} = \frac{- 8}{3}$

$\therefore\text{ L . H . S . = R . H . S . for }x = \frac{- 118}{39}$

Is there an error in this question or solution?

#### APPEARS IN

RD Sharma Class 8 Maths
Chapter 9 Linear Equation in One Variable
Exercise 9.3 | Q 23 | Page 17